Fotointerpretación y observaciones de campo del flujo de escombros de noviembre 13 de 1985 en armero (tolima, colombia) (1995)
The photointerpretation, using aerial photographs recorded from the Armero's Debris Flow, few days after it took place, in agreement with survivors reports, indicate that the event occurred in three principal pulses, each one with different hydrodynamic characteristics, as has been observed in other places of the world. In the first place there was a preceding muddy flow that only affected the shallower places such as the closer ones to the Lagunilla River; the first pulse was an extremely dense flow supersatured with solids with a variable and relatively low velocity that resulted in a continous debris sheet that covered the flat lands with a thickness of up to 3 meters height and a radius of 2.5 km. The push and advance of this flow which included the biggest blocks was the responsible of the destruction of Armero. The effect of this flow was differential, as in higher zones the debris flow did not demolish houses and was inyected though doors and windows. The high density of this flow was one of the main reasons that it did not affect some streets with high slopes.  The second pulse consisted of high velocity turbulent running water, loaded with pebbles and gravels, which generated a high erosion capacity that stripped off the former fan, providing a terrace aspect and producing new distributary water channels. The third pulse was a low level water flow with a high concentration of gravel, sand and mud, which took place for several hours. It was concluded, from the photointerpretation, that the Armero's Debris Row according to its hydrodynamic characteristics, reached the flatter topography and overflowed the Lagunilla's riverbed at different places.